Organizational and Institutional Behavior in Pondok Pesantren with The Integrated Model - Dadan Sunandar; Abdul Rosyad (Budapest International Research and Critics University, 2022)
Today, there are many discourses related to the swift currents of change, pesantren still survive with the enthusiasm and high tradition/culture that is amazing. In the view of Muslims, it seems that Islamic boarding schools have been considered models of educational institutions that have advantages both from the aspect of the scientific tradition which is one of the great traditions, both in terms of transmission and internalization of the morality of Muslims. In this research, organizational behavior in Islamic boarding schools is based on the opinion of Colquitt, Lapine Weson, quoted by Siswoyo H & Halim P, that an integrative/combined model of organizational behavior was developed to improve three main goals including 1) organizational behavior; 2) individual performance; 3) Organizational commitment. Rist is through a literature study approach through various media related to